THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND MEDICATION ADHERENCE IN SCHIZOPHRENIA PATIENTS - Nadia, Nyayu; Andre Utama Saputra; Sasono Mardiono; Selamat Parmin (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Mental disorders that are found worldwide include schizophrenia. The causes of schizophrenia can be influenced by genetic factors, stress, and environmental factors such as past trauma, interpersonal issues, family problems, failure to achieve goals, and economic pressures. The recovery of patients can also be influenced by their adherence to the treatment process. This study aims to determine the relationship between family support and medication adherence in schizophrenia patients at the Poli Klinik RS Ernaldi Bahar in South Sumatra Province. This study uses a quantitative approach with a cross-sectional design. The sampling technique used is purposive sampling with a sample size of 99 respondents. Data collection for this study was done using a questionnaire. The results show a significant relationship between family support and medication adherence in schizophrenia patients at the Poli Klinik RS Ernaldi Bahar in South Sumatra Province, with a p-value of 0.000. There is a relationship between family support and medication adherence in schizophrenia patients. It is recommended that family members always provide support and motivation to patients.